The Influence of Emotional Intelligence and Quality of Work Life on Employee Performance at Platinum Gadget Malang - Nengsih, Ifelda; Rani , Wahyu Mustika; Dewi, Mariana Puspa (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
Employee performance is a crucial element for the sustainability of companies, especially in the service sector. This study aims to examine the influence of emotional intelligence and quality of work life on employee performance at Platinum Gadget Malang. A quantitative research method was employed, using a survey approach and a saturated sampling technique that involved all 36 employees as respondents. Data analysis was conducted using multiple linear regression with SPSS version 27. The results indicate that both Emotional Intelligence (β = 0.487, p < 0.05) and Quality of Work Life (β = 0.376, p < 0.05) have a positive and significant effect on employee performance. The coefficient of determination (R²) is 0.584, which means that 58.4% of performance variation can be explained by these two independent variables. These findings highlight the importance of open communication and a supportive work environment in enhancing performance. The implications of this study are valuable for human resource management, especially in efforts to improve employee welfare and productivity.